Implementation of the system approach in the development of radar meteorological monitoring system - Perelygin, B.V. (Radiotekhnika, 2017)
The principles of building existing radar meteorological networks are analyzed. The necessity of a systematic approach to the construction of a radar system for meteorological monitoring is substantiated. The methodology of applying a systematic approach to the construction of a radar meteorological monitoring system is formulated. The results of the simulation of the radar system for meteorological monitoring are presented.